The use of calf compresses for gentle fever reduction- What do we know? A scoping review. Issue 5 (October 2022) - Raak, Christa; Scharbrodt, Wolfram; Berger, Bettina; Boehm, Katja; Martin, David
Abstract: Background: Compresses are one of the water treatments of Traditional European Medicine and are used for a variety of indications in patient care. Calf compresses are used for gentle fever reduction. However, little is known about the origin and effectiveness of calf compresses. Aim: We aimed to provide an overview regarding the evidence of the effects of the use of calf-compresses to reduce fever by means of a scoping review. Methods: Five electronic databases and the "Library of the Institute for the History of Medicine" were searched in English and German language. Gray literature was also considered. The "PRISMA Scoping Review Guideline" was applied for the methodological preparation of the review. Results: 45 articles were included and divided into the sections history and origins (eight references), nursing guidance (eight references), trials regarding nursing inpatients (13 trials), and trials regarding patients at the Intensive Care Unit (16 trials). While several articles and trials regarding the use of sponging and other cooling strategies were available, the use of calf-compresses was only found in a minority of German speaking articles. Only two studies demonstrated the use of calf-compresses for gentle fever reduction. Overall, the literature and studies found a support for physical cooling practices mostly along with pharmacologic antipyretics. The way of cooling, cooling application temperatures, duration of applications and the definition of fever at all demonstrate controversy approaches of methods. In clinical trials worldwide, physical cooling to lower fever is associated with side effects and discomfort. Conclusion: Calf compresses are well established in German-speaking countries. Based on the knowledge gaps identified in this scoping review, further studies would be needed to explore calf compresses in their antipyretic properties and in particular their mode of application including physiological considerations. Observation to fever onset and/or phases could be an identified key useful starting point for future research. Contraindications to a fever-reducing calf wrap must be strictly observed.